Assessing how a teaching professional development program for biology graduate students bolsters self-efficacy and shapes teaching perspectives - Anisha S. Navlekar; Nia Baker; Mackenzie Ghaemmaghami; Imani Obasi; Sochinenyenwa Onubogu; Cassandra O'Pry; Robert Posey; Jessica Tan; Karen Walulu; Joshua W. Reid; Lisa B. Limeri (Journal of Microbiology & Biology Education)
ABSTRACT Graduate teaching assistants (GTAs) teach undergraduates directly, and many are future faculty, making it particularly important for them to be trained in using evidence-based instructional practices. We implemented and assessed a teaching professional development program for 19 biology GTAs aimed to help them develop their teaching perspectives and improve their teaching self-efficacy. The program consisted of a pre-semester bootcamp of pedagogical workshops, mentoring sessions throughout the semester, crafting a teaching philosophy statement, and reflective peer teaching observation. We surveyed and interviewed students throughout the program to assess their growth and identify elements of the program that supported their growth. We found that participants’ self-efficacy improved immediately following the pre-semester bootcamp, but these improvements did not persist throughout the semester. At the end of the semester, participants’ teaching self-efficacy did not differ from GTAs in the department who did not participate in our program. Throughout the semester, our participants shifted toward the social reform perspective of teaching, which views good teaching as encouraging students to critically evaluate information and give them power to take social action to improve their lives. At the end of the semester, our participants more strongly endorsed the social reform perspective of teaching than GTAs who did not participate in our program. Our results suggest that pre-semester workshops supported novice GTAs before their class, but more sustained interactions may be needed for these boosts to persist. Our results also suggest that encouraging GTAs to reflect on what makes good teaching can help them solidify a coherent teaching perspective.